Characteristics of the structure and composition of the oropharyngeal microbiota in patients with acute tonsillitis depending on smoking status - Kravets, Nataliia (ScienceRise: Biological Science, 2025)
The aim of the study was to compare alpha and beta diversity indices, assess the overall structure and identify taxa of the oropharyngeal microbiota in patients with acute tonsillitis under the influence of smoking. Materials and methods. 54 samples of oropharyngeal swabs from patients with acute tonsillitis were analyzed, which were divided into groups, namely Group 1 (26 people), who smoked, and Group 2 (28 people), who did not smoke. To assess alpha diversity, the Shannon, Simpson, Pielu, Fisher and Chao-1 indices were used, for beta diversity, the Whittaker, Harrison, Wilson-Schmidt and Bray-Curtis indices. The PAST v.4.03 program was used with PERMANOVA, ANOSIM (9999 permutations) and SIMPER statistical analysis. Results. Analysis of the results of alpha-diversity indices did not reveal statistically significant differences between groups (p > 0.05). The results of beta-diversity indices demonstrated a greater diversity of microbial communities in group 1 (smokers) (Whittaker indices 3.59 vs. 3.05; Harrison indices 0.33 vs. 0.28). The results of multivariate analyses (PERMANOVA, ANOSIM) did not reveal statistically significant differences in the structure of the microbiome of patients with tonsillitis (p > 0.05). SIMPER analysis demonstrated that α-hemolytic streptococci (20.28%), Neisseria spp. (19.59%) belong to taxa responsible for 74.58% of the total intergroup differentiation of the oropharynx, however, they show different colonization densities (5.15 in smokers vs. 4.96 in non-smokers for α-hemolytic Streptococcus spp. and 1.50 in smokers vs. 2.21 in non-smokers for Neisseria spp.) Conclusion. Regardless of smoking status, the oropharyngeal microbiota of patients with acute tonsillitis is characterized by taxa similarity. However, in patients who smoke, increased variability of microbial communities is observed, in particular, a decrease in commensal bacteria of the genus Corynebacterium spp., a tendency to increase β-hemolytic streptococci and the appearance of fungi of the genus Candida spp., which may affect the course of the inflammatory process